INTEGRATION OF THE MAQASHID SHARIAH INDEX AND THE RGEC METHOD IN ASSESSING THE FINANCIAL PERFORMANCE OF ISLAMIC BANKS - Fitriani Arief; Muhammad Wahyuddin Abdullah; Amiruddin K; Kurniawati Meylianingrum; Muhammad Nur Alam Muhajir (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This study aims to describe the integration between the Maqasid Sharia index and the REGC method in assessing the financial performance of Islamic banks. This research is a descriptive research that aims to explore, compile, and analyze various information available in written sources related to the research topic. The source of data in this research is obtained from literature study which includes various literatures relevant to the research topic. Data collection is done by reviewing existing literature in various sources of books, articles and documents. From the results of the analysis, it will be arranged how the integration of the Sharia Maqashid index with the RGEC method can be applied in assessing the financial performance of Islamic banks. This research shows that the integration of maqashid sharia index with RGEC method in the assessment of financial performance of Islamic banks provides a more comprehensive and fair approach. The assessment of Islamic banks is not only based on financial aspects, but also on their contribution to social welfare and compliance with sharia principles. The integration between maqashid sharia index and RGEC method is very relevant to ensure that Islamic banks are not only financially profitable, but also provide a positive impact in social and ethical aspects, in accordance with sharia principles. It is expected that the results of this study can contribute to the development of Islamic banking theory by offering a new approach in assessing the performance of Islamic banks in line with the objectives of Islamic banks, namely the welfare of the people and social benefit.